Visualization of Carbon Nanotube Aggregates in Dilute Phase of a Fluidized Bed - Han Park, Sae; Won Kim, Sung (International Journal of Engineering and Technology, 2018)
Background/Objectives: Fluidization characteristics and aggregation behavior of carbon nanotube (CNT) particles have been determined in the freeboard of a bubbling fluidized for the design and scale-up of the process.Methods/Statistical analysis: The aggregation behavior of the CNT particles was observed in a gas solid fluidized bed (0.15 m i.d. X 2.6 m high) using laser sheet technique for their visualization. A high speed camera was installed at the height of 0.67, 1.05 and 1.50 m above the gas distributor to observe the CNT aggregates behavior and determine their size and shape. The Image J was applied to process the obtained images.Findings: Effect of height in the reactor on aggregation of CNT particles have been determined. The axial local bulk density distribution is almost similar with a general bubbling fluidized bed such as Geldart A or Geldar B particles, which shows typically a dense bed at the bottom of the reactor and a decrease of the local bulk density with increasing height. The Feret and Heywood diameters of the aggregates are larger than the average diameter of the CNT particles, indicating that the CNT particles form the aggregates by physical entanglements and van der Waals force in the dilute phase of fluidized bed. A possible mechanism of aggregates formation was proposed based on the variation of size and shape of CNT aggregation with the height. The aggregation process in dilute phase is attributed largely to nanotubes stripping off the surface of CNT particles in addition to the inter-particle aggregation. The aggregation process affects the decrease of aspect ratio and the increase of solidity of aggregates with increasing the height.Improvements/Applications: The obtained results on the CNT properties could be used for the design of cyclone and the modeling of heat transfer in the fluidized bed reactor.Â Â